2021
DOI: 10.1021/acs.jafc.1c01781
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Microbiome-Derived Inosine on Lipopolysaccharide-Induced Acute Liver Damage and Inflammation in Mice via Mediating the TLR4/NF-κB Pathway

Abstract: This research assessed the anti-inflammatory and hepatoprotective properties of inosine and the associated mechanism. Inosine pretreatment significantly reduced the secretion of several inflammatory factors and serum alanine transaminase (ALT) and aspartate amino transferase (AST) levels in a dose-dependent manner compared with the lipopolysaccharide (LPS) group. In LPS-treated mice, inosine pretreatment significantly reduced the ALT and malondialdehyde (MDA) concentration and significantly elevated the antiox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
72
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 102 publications
(80 citation statements)
references
References 54 publications
(101 reference statements)
7
72
0
1
Order By: Relevance
“…6 A). It was previously reported that the abundance of Marvinbryantia was positively correlated with the level of cecal SCFAs and negatively related to the total antioxidant capacity of liver in LPS-treated mice ( Guo et al, 2021 ). Tyzzerella and Peptococcus are beneficial to inhibit the development of inflammation and ameliorate the host immunity, partly due to the inhibition of the secretion of lipopolysaccharide, D-lactic acid and TNF-α ( Huang et al, 2021b ).…”
Section: Resultsmentioning
confidence: 94%
“…6 A). It was previously reported that the abundance of Marvinbryantia was positively correlated with the level of cecal SCFAs and negatively related to the total antioxidant capacity of liver in LPS-treated mice ( Guo et al, 2021 ). Tyzzerella and Peptococcus are beneficial to inhibit the development of inflammation and ameliorate the host immunity, partly due to the inhibition of the secretion of lipopolysaccharide, D-lactic acid and TNF-α ( Huang et al, 2021b ).…”
Section: Resultsmentioning
confidence: 94%
“…g_ Marvinbryantia and g_ Defluviitaleaceae_UCG-011 was negatively correlated with IL-6; g_ Marvinbryantia spp. could inhibit the host inflammation by producing SCFAs ( 31 ); It has been reported that the abundance of g_ Defluviitaleaceae_UCG-011 was decreased in oral of rheumatoid arthritis patients ( 32 ).…”
Section: Resultsmentioning
confidence: 99%
“…The severity of colitis can be mitigated by reducing them ( 60 , 61 ), which provides us another potential mechanism for the treatment of colitis by melatonin. Additionally, Lachnospiraceae_UCG-006 is related to short-chain fatty acid metabolism, which may participate in the process of colitis and liver inflammation ( 62 , 63 ). Accordingly, the transplantation of feces from melatonin-treated mice mitigates Oxa-induced colitis, validating that melatonin alleviates type 2 immunity-related colitis in a microbiota-dependent manner.…”
Section: Discussionmentioning
confidence: 99%